Guide for Designing Mandatory Greenhouse Gas Reporting Programs - Singh, Neelam (World Bank, Washington, DC, 2015)
Over the past decade, greenhouse gas reporting programs have emerged to provide information on emission sources and trends. As more jurisdictions plan to design and implement these programs, this report draws on the experience of 13 existing and proposed programs to guide policymakers and practitioners in developing such GHG reporting programs. Business, industry associations, civil society and funding agencies may also find this guide useful in facilitating their participation in the development of a reporting program. The guide provides step by step guidance on the four basic steps to design a reporting program: determining program objectives; creating an enabling environment for program design and implementation; determining program structure and requirements; and conducting program review.